Potential involvement of C3 complement factor in amphibian fertilization - Llanos, Ricardo Javier (2000)
We have assessed the potential involvement of C3, the third complement factor, and its receptor in Bufo arenarum fertilization. We show that a polyclonal antibody against a B. arenarum C3-like factor (C3Ba) reacts specifically with components of the extracellular matrix (ECM) of coelomic eggs and the cell membrane of uterine eggs. Interestingly, we have identified a 163 kD protein immunoreactive with a monoclonal antibody against the CD11b α chain of the human C3 receptor on the cell membrane of the animal pole of uterine eggs, the site of entry of the sperm, but not in coelomic eggs (CR3Ba). Treatment of coelomic eggs with a pars recta oviductal-like protease, trypsin, induced the translocation of C3Ba from the ECM to the cell membrane. Furthermore, inhibition of CR3Ba by trypan blue, as well as inhibition of C3Ba by anti-C3Ba on uterine eggs impaired fertilization, whereas identical treatment on sperm cells did not alter percentage fertilization. Our results suggest, (A) that changes in the localization of C3Ba from the ECM to the cell membrane may be triggered by trypsin-like proteases during passage of eggs through the oviduct; and (B) that C3Ba/CR3Ba may be involved in B. arenarum fertilization.